2000
DOI: 10.1108/09513550010356520
|View full text |Cite
|
Sign up to set email alerts
|

The capacities needed by local authority chief executives

Abstract: Research was commissioned to identify the competences that are required by local authority chief executives in the UK. It emerged that the “competence approach” was inappropriate for their needs. Instead, “capacity” – a concept originating in psychoanalytic theory – was adopted as one which reflected better the reality of the chief executive’s role. Through a qualitative research approach with a sample of chief executives, five capacities were identified. These were seen as central to the effective performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…The third area for the CEO is the ‘political edge’, which is all of the elected officials and politicians both on the council and in other tiers of government. Broussine (), building on Mintzberg's model, highlights that while each of the three dimensions requires certain technical competencies, the important CEO attributes are ‘capabilities’ that allow for working between the three dimensions to ensure a balance of between the concerns of different stakeholder interests and political perspectives (Broussine, : 502).…”
Section: The Role Of the Local Government Ceomentioning
confidence: 99%
See 1 more Smart Citation
“…The third area for the CEO is the ‘political edge’, which is all of the elected officials and politicians both on the council and in other tiers of government. Broussine (), building on Mintzberg's model, highlights that while each of the three dimensions requires certain technical competencies, the important CEO attributes are ‘capabilities’ that allow for working between the three dimensions to ensure a balance of between the concerns of different stakeholder interests and political perspectives (Broussine, : 502).…”
Section: The Role Of the Local Government Ceomentioning
confidence: 99%
“…This article draws on findings from a recent study that aims to understand more about the conceptualisation of leadership in local government by recognising what qualities, experiences and attributes elected officials value in the CEO, and what policies and strategies they apply to identify and recruit suitable candidates. The article is organised to first review the relevant literature about the role of the CEO within the context of contemporary Australian local government and draws on literature both international and Australian that covers a range of issues related to leadership in local government including the changing nature of the sector (Aulich and Artist 2015;Fox and Leach 1999;Jones 2011), roles of, and relationships between CEOs and Mayors (Jones 2011;Martin and Aulich 2012), leadership styles (Martin and Simons 2002;Svara 2001Svara , 2003, leadership capabilities and capacities (Broussine 2000;Mintzberg 1998), and diversity (Diamond 2008;Hutchinson et al 2014). Second, the research method is described, followed by a summary and analysis of the data gathered from a series of interviews with Western Australian CEOs and Mayors/Shire Presidents.…”
Section: Introductionmentioning
confidence: 99%
“…The earlier research for SOLACE identified the capacity for maintaining personal perspective and self-knowledge as one of the five capacities which were thought central to the chief executive's effectiveness (Broussine, 2000). To repeat an earlier point, a person who can work effectively at the boundary is trying continuously to make sense of what is going on there in a situation of flux.…”
Section: Maintaining Personal Perspective and Self-knowledgementioning
confidence: 97%
“…The capacity 'to develop effective external relationships' was one of the five key capacities uncovered in the earlier research for SOLACE (Broussine, 2000). That capacity included a number of descriptors which included 'Being a champion of the local authority, local government and local democracy' and 'Working with communities and other agencies'.…”
Section: Duality In the Role Of Chief Executivementioning
confidence: 99%
See 1 more Smart Citation